2022
DOI: 10.1093/ejcts/ezac464
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cystic adenomatoid malformations of the lung: a retrospective study of diagnosis, treatment strategy and postoperative morbidity in surgically treated patients

Abstract: Objectives The purpose of this study was to evaluate diagnosis, clinical signs and strategy in Congenital Cystic Adenomatoid Malformations (CCAM). Methods In this retrospective study, patients with thoracic surgery for CCAM lesions at the University Hospitals of Leuven from July 1993 to July 2016 were searched. Data on diagnosis, prenatal ultrasound findings, clinical signs, lesion site, CCAM type, associated anomalies, imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…An imaging examination should be performed during the follow-up after birth for those with prenatally identified lesions by ultrasound, and it is necessary to comprehensively consider the radiation dose for the child and the family’s assessment of the risk and choose the operation according to the change of the condition. Verhalleman indicated that in his university hospital, if possible, the first 3 months of life are preserved for lung growth and general development ( 4 ). Elective surgery in patients with a high risk for clinical symptoms is recommended before 12 months of age, although no specific guidelines exist ( 5 - 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An imaging examination should be performed during the follow-up after birth for those with prenatally identified lesions by ultrasound, and it is necessary to comprehensively consider the radiation dose for the child and the family’s assessment of the risk and choose the operation according to the change of the condition. Verhalleman indicated that in his university hospital, if possible, the first 3 months of life are preserved for lung growth and general development ( 4 ). Elective surgery in patients with a high risk for clinical symptoms is recommended before 12 months of age, although no specific guidelines exist ( 5 - 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CPAM accounts for about 1/35,000–1/7,200 of the live fetuses, and this rate is gradually increasing ( 2 ). For asymptomatic children with CPAM after birth, the appropriate age for operation is above 3 months old ( 3 , 4 ). Notably, a few children were born with serious respiratory and circulatory disorders due to the compression of the heart and lungs and mediastinal deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal steroids, thoraco-amniotic shunts, fetal mass resection, and ex utero intrapartum treatment (EXIT) procedures play a significant therapeutic role in congenital lung lesions with hydrops, resulting in lower risk of prematurity, less ventilator requirement, and a better outcome, compared to open or minimally invasive fetal surgery (18)(19)(20)(21)(22).…”
Section: Prenatal Treatmentsmentioning
confidence: 99%
“…In macrocystic lesions, thoracocentesis or thoraco-amniotic shunting are useful for both diagnosis and treatment of hydrops. The indications for open fetal surgery are hydrops and signs of evolving fetal heart failure (20).…”
Section: Prenatal Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation